Ecosystem services and agroforestry a sustainable future ahead - Kaur, Navneet; Thakur, Sapna; Kaur, Ramanjit (Indian Farming, 2018)
In this era of environmental consciousness and ecological sustainability, agroforestry has been considered as panacea for all the environmental and socio-economic problems. This climate resilient land use practices offers various tangible and intangible benefits. The quantification and evaluation of ecosystem services such as carbon sequestration, soil enrichment, biodiversity conservation, air and water quality improvement provided by agroforestry systems will boost the acceptability of the system as climate smart practice.